Model Peningkatan Customer Loyalty Melalui Customer Satisfaction, Product Innovation dan Selling Experience - Fernandy Setiawan (Journal of Economic and Business Advancement, 2026)
This study aims to analyze the influence of product innovation and selling experience on customer loyalty, with customer satisfaction serving as a mediating variable, among consumers of coffee-related SMEs in Semarang City. The study was motivated by the intense competition in the coffee shop industry, which requires business owners to maintain customer loyalty through product innovation and superior purchasing experiences. The research employed a quantitative approach, specifically explanatory research. Data were collected via a Likert-scale questionnaire and analyzed using Structural Equation Modeling based on Partial Least Squares. The results indicate that product innovation and selling experience have a positive and significant effect on customer satisfaction. Customer satisfaction was also found to have a positive and significant effect on customer loyalty. Product innovation and selling experience also have a direct effect on customer loyalty.